(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
‘Blame shifting’ or ‘deflection’ is generally a psychological process where something is passed over to someone else in an attempt to draw attention away. It is a type of defense regarded as emotionally unmannerly. But in this paper, blame shifting has been presented as a positive aspect, representing a general phase that children go through during their first language acquisition period. When children acquire meaning, they shift blame, that starts as a psychological process but linguistically represents the creative use of language in different ways. In this paper, I tried to present the phase of blame shifting of ten participant children as a medium of meaning construction in their first language acquisition process. In an attempt to break the stereotypical assumption of the term ‘blame’, this paper would try to reflect how children shift blame on others as a part of their language development by manipulating language use and cognitive intelligence. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 99-118